Recommendations of the Sardinian public for the treatment of depression. (November 2014) - Carta, Mauro G; Angermeyer, Matthias C; Matschinger, Herbert; Holzinger, Anita; Pintus, Elisa; Pintus, Mirra; Moro, Maria F
Background: Public beliefs about appropriate treatment impact, help-seeking and treatment adherence. Aim: To determine the recommendations of the Sardinian public for the treatment of depression. Methods: In 2012, a population-based survey was conducted by phone in Sardinia ( N = 1, 200). In the context of a fully structured interview, respondents were presented with a vignette depicting a case of depression. Subsequently, they were asked about their treatment recommendations. The results are contrasted with findings from a similar survey which had been conducted in Vienna 3 years before. Results: In Sardinia as in Vienna, psychotherapy was the uncontested favorite, while antidepressant medication was recommended by relatively few respondents. In Sardinia, there were also no marked differences between urban and rural areas with regard to these two treatments. However, between Sardinia and Vienna, as well as within Sardinia, great differences were found with regard to autogenic training and 'alternative' methods like homeopathic medicines and acupuncture. Conclusion: Cross-cultural comparisons may help better understand treatment preferences of the public. In Sardinia, as in Vienna, there seems to be a need for improving the public's knowledge about the appropriate treatment of depression.